P191 Drug survival of biologics in Crohn's disease treatment in Norway. (25th January 2019) - Lirhus, S S; Lie Høivik, M; Moum, B; Melberg, H O
Abstract: Background: Real-world treatment patterns of biologics remains largely unknown. We aimed to investigate the drug survival of biologics in a national cohort of patients with Crohn's disease (CD). Methods: Data were collected from the Norwegian Patient Registry (NPR) and the Norwegian Prescription Database. The study cohort was defined as all patients with at least two diagnosis of K50 (CD) in NPR from 2010 to 2017 with no prior IBD diagnosis in NPR (data from 2008). Treatment for patients who only received one infusion of vedolizumab or infliximab before discontinuing treatment was not included in the analysis to exclude false registrations. Vedolizumab is not given as first-line biologic treatment in Norway due to the tender process. Kaplan–Meier time‐to‐event analyses were performed to estimate time to treatment discontinuation. Discontinuation was defined as 3 months without a new infusion or prescription of the current drug after the predefined DDD period for the drug (i.e medication gap of >90 days). Biologic survival was compared using the log-rank test. The proportion of patients that received methotrexate or azathioprine was estimated by looking at the number of patients who received a prescription of an immunomodulator 6 months prior to or after starting biologic treatment. The chi-square test was used to compare the proportions receiving immunomodulators. Patients were followed until the outcomes of interest, death, or end of follow-up (31 December 2017), whichever occurred first. Results: In total, 2444 CD patients were included in the study. After 3 years, the survival rate of first-line biologics for CD patients was 50.3% for infliximab and 40.5% for adalimumab ( p < 0.001). For second-line treatment, the survival rates were 42.4% for infliximab, 42.8% for adalimumab and 69.8% for vedolizumab. Vedolizumab survival was significantly different compared with adalimumab and infliximab ( p < 0.001). 72.4% of infliximab patients and 56.6% of adalimumab patients received an immunomodulator 6 months before or after starting treatment ( p < 0.001). Conclusions: In this Norwegian real-world registry study of CD patients, drug survival for biologics differed significantly in both first and second-line treatment.